Impact of Using Processed Urinary Bladder Submucosa and Hydrogel Fabricated from Tendon on Skin Healing Process in Rabbits - Majid A. Alkhilani; Omar Tariq Hammoodi; Hasanain Abduljabbar Emran; Wissam Abdullah Alhayani (Veterinary Medicine International)
This study was intended to evaluate the healing of skin injury by using decellularized urinary bladder submucosa scaffolds and tendon-derived hydrogel. Thirty-six adult local breeds of both sex rabbits, with an average weight of 2.0–2.5 kg, were divided randomly into three groups (12 animals for each group). All groups were subjected to an induced injury (2 cm) in diameter at the right side of the abdominal skin, the rabbits of the 1st group (A) were sutured without the application of any substance as a control group, the rabbits of the 2nd group (B) were sutured and treated with the application of decellularized urinary bladder submucosa scaffolds, and in the 3rd group (C), they were sutured and treated with the application of tendon-derived hydrogel. Postoperative care following had been done for all groups throughout the study period. Specimens from the injured skin were taken for the histopathological study on the postinjury day, 8th, 14th, 21st, and 24th. The study showed a clear effect of materials used in the treatment of wounds through a clear progression in the healing stages with a noticed superiority of the submucosa scaffold group.